Stable Down-Regulation of HLA Class-I by Serum Starvation in Human PBMCs - Mahsa Rahmani (Iranian Journal of Immunology, 2016)
Background: The human leukocyte antigen (HLA) matching between organ donor and recipient is an acceptable strategy in clinical transplantation since 1964. However, in bone marrow transplantation, finding matched donors is often problematic. Thus new method for down regulation of HLA can be an alternative strategy to solve this problem. Objective: To examine the effect of serum starvation on HLA class I expression in human peripheral blood mononuclear cells (PBMCs). Methods: PBMCs were cultured in RPMI-1640 supplemented with 10% FBS (non-starved cells) as well as in medium only (starved cells) for 16, 24, 48, 72, 96h under standard cell culture conditions. The pattern of cell death and HLA class I expression was determined by flowcytometry. Antigenicity of the starved PBMCs was evaluated in a one-way mixed lymphocyte culture by MTT assay. Results: Mean fluorescence intensity (MFI) of different indicated starved PBMCs gradually decreased and this reduction was stable after 96h of re-feeding with medium containing FBS. Under serum starvation condition, PBMCs showed apoptotic cell death pattern. There was a linear correlation between percentages of cells, which exhibited the late apoptosis death pattern and serum starvation period (r=0.88, p<0.01). Surprisingly, the starved PBMCs lost their stimulatory property in mixed culture with allo-reactive lymphocyte. Conclusions: Membrane HLA class I expression could be stably reduced in 96h starved human PBMCs culture condition, decreasing their allo-reactivity while their viability rate is enough for possible clinical application.